2010
DOI: 10.1007/s10067-010-1629-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased need of large joint replacement in patients with rheumatoid arthritis in a specialized Brazilian center

Abstract: Disease-modifying antirheumatic biological and non-biological therapies are associated with reduced disease progression and joint destruction. Suggestions have been made that total knee and hip joint arthroplasty indications are decreasing as a beneficial effect of the new forms of therapy for rheumatoid arthritis. We present findings of our institution on the incidence of joint arthroplasty in the past few years in patients with rheumatoid arthritis and the increase in the numbers of procedures not associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…In the literature, few inception cohorts of early RA had assessed rates of orthopedic and small joint surgery, with conflicting results [ 9 14 , 18 , 19 ]; prevalence ranged from 5.3% at a mean follow-up of 4.6 years [ 13 ] to 58% after a mean follow-up of 16 years [ 12 ]; variations may be explained by a lack of a uniform definition of “early disease” [ 9 14 , 19 ], a wide spectrum of follow-ups that may last up to 25 years [ 19 ], differences in the genetic background of the populations in whom surgery was assessed (from the UK [ 9 , 11 , 14 ], Sweden [ 12 , 18 ], Canada [ 13 ], the Netherlands [ 10 ] and Finland [ 19 ]) and the year of patient’s inclusion, which may have affected the current standard of care. Our cohort had distinctive characteristics which may additionally explain our low OHSI prevalence, estimated as 2.2% at 5 years and reaching 11.7% at last follow-up (13 years); all of our patients were of Hispanic origin and there is only one study which evaluated 355 major joint surgeries performed in Brazilian patients, although only 8 patients had RA diagnosis, which precludes any comparison [ 20 ]; also, mean symptom’s duration from our patients was close to 5 months, the cohort had a limited follow-up and included patients from 2004 onwards; finally, our patients received a T2T strategy, primarily with combined traditional DMARDs meanwhile only 4 patients had access to biologics. Of note, Moura et al [ 13 ] identified new-onset RA patients in the Québec Health Insurance Program databases from 2002 to 2011, which is close to our cohort initiation date, and described 10.9 joint replacements during 1000 person-years, similar to our finding.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, few inception cohorts of early RA had assessed rates of orthopedic and small joint surgery, with conflicting results [ 9 14 , 18 , 19 ]; prevalence ranged from 5.3% at a mean follow-up of 4.6 years [ 13 ] to 58% after a mean follow-up of 16 years [ 12 ]; variations may be explained by a lack of a uniform definition of “early disease” [ 9 14 , 19 ], a wide spectrum of follow-ups that may last up to 25 years [ 19 ], differences in the genetic background of the populations in whom surgery was assessed (from the UK [ 9 , 11 , 14 ], Sweden [ 12 , 18 ], Canada [ 13 ], the Netherlands [ 10 ] and Finland [ 19 ]) and the year of patient’s inclusion, which may have affected the current standard of care. Our cohort had distinctive characteristics which may additionally explain our low OHSI prevalence, estimated as 2.2% at 5 years and reaching 11.7% at last follow-up (13 years); all of our patients were of Hispanic origin and there is only one study which evaluated 355 major joint surgeries performed in Brazilian patients, although only 8 patients had RA diagnosis, which precludes any comparison [ 20 ]; also, mean symptom’s duration from our patients was close to 5 months, the cohort had a limited follow-up and included patients from 2004 onwards; finally, our patients received a T2T strategy, primarily with combined traditional DMARDs meanwhile only 4 patients had access to biologics. Of note, Moura et al [ 13 ] identified new-onset RA patients in the Québec Health Insurance Program databases from 2002 to 2011, which is close to our cohort initiation date, and described 10.9 joint replacements during 1000 person-years, similar to our finding.…”
Section: Discussionmentioning
confidence: 99%
“…One 18-year longitudinal study published in 1998 estimated that 25% of all patients with RA required total joint replacement surgery [ 10 ]. However, the incidence of joint replacement surgery in patients with RA has decreased in recent years, primarily because of the development of more effective medical treatment [ 11 13 ]. In a Norwegian register-based study, Nystad and Fenstad reported a decrease in the incidence of orthopedic surgery in patients with RA that continued into the era of biologics.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of targeted biologic therapies has revolutionized the treatment of immune inflammatory arthritis [ 1 ]. The use of such compounds has significantly improved patient outcomes and decreased the need for surgical procedures to repair damaged joints [ 2 ]. The use of tumor necrosis factor (TNF) antagonists has proven successful since their introduction in 1999.…”
mentioning
confidence: 99%